1995
DOI: 10.1111/j.1348-0421.1995.tb03272.x
|View full text |Cite
|
Sign up to set email alerts
|

Class‐Specific Antibody Response in Acyclovir‐Treated and Adenine Arabinoside‐Treated Patients with Primary Genital Herpes Simplex Virus Infection

Abstract: Herpes simplex virus (HSV) class-specific antibody responses after primary genital herpes infection were evaluated with an enzyme-linked immunosorbent assay (ELISA) in 16 patients treated with acyclovir (ACV), given orally, and 17 patients treated with adenine arabinoside (Ara-A), given topically. ACV significantly suppressed the levels of IgM, IgA, and IgG. In the ACV-treated patients, IgM and IgG were not detected in 4 of the 16 and in 1 of the 16 patients, respectively. We must take into account this suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…This is consistent with clinical results in patients undergoing acyclovir treatment, as reported by Lafferty et al (1984) and Mitchell et al (1986). Clinical observations concerning the immune response of HSV-infected patients showed a lower antibody titre in acyclovir-treated patients than in placebo-treated patients, resulting in suppression of antibody response or lymphoproliferative responses to HSV (Ashley & Corey, 1984;Bernstein et al, 1984;Lafferty et al, 1984;Mitchell et al, 1986;Erlich et al, 1988;Gold et al, 1988;Ragab et al, 1989;Kawana et al, 1995;Hu et al, 1997). Results of the present study would be applicable in interpreting those observations, although it is difficult to deny the possibility that antibody titre is dependent on the severity of skin lesions.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This is consistent with clinical results in patients undergoing acyclovir treatment, as reported by Lafferty et al (1984) and Mitchell et al (1986). Clinical observations concerning the immune response of HSV-infected patients showed a lower antibody titre in acyclovir-treated patients than in placebo-treated patients, resulting in suppression of antibody response or lymphoproliferative responses to HSV (Ashley & Corey, 1984;Bernstein et al, 1984;Lafferty et al, 1984;Mitchell et al, 1986;Erlich et al, 1988;Gold et al, 1988;Ragab et al, 1989;Kawana et al, 1995;Hu et al, 1997). Results of the present study would be applicable in interpreting those observations, although it is difficult to deny the possibility that antibody titre is dependent on the severity of skin lesions.…”
Section: Discussionsupporting
confidence: 79%
“…However, the correlation between the severity of skin lesions and the level of the cellmediated and humoral immune responses is poorly documented. Some researchers have demonstrated that acyclovir can reduce the rise in antibody production on infection when compared with placebo treatment (Ashley & Corey, 1984;Bernstein et al, 1984;Erlich et al, 1988;Gold et al, 1988;Ragab et al, 1989;Kawana et al, 1995;Hu et al, 1997). Other researchers have found that both the lymphocyte proliferative response and antibody production were lower in acyclovir-treated patients compared to placebotreated patients (Lafferty et al, 1984;Mitchell et al, 1986).…”
mentioning
confidence: 99%
“…Several reports including ours revealed that acyclovir treatment suppresses the production of HSV-specific antibody and lowers the antibody responses, especially that of IgM, in primary HSV infection (2,4,18). Therefore, it is noteworthy that the sera used here were collected during 1972 to 1985 from the patients under no influence of any antiviral treatment, and that the results obtained describe the natural course of the humoral immune response in genital HSV infection, although the number of cases examined was small.…”
Section: Discussionmentioning
confidence: 86%
“…Samples were assayed using two enzyme-linked immunosorbent assay (ELISA) kits, the Herpes Simplex IgG detection kit and Herpes Simplex IgM detection kit (Denka Seiken, Tokyo, Japan), which detect IgG and IgM antibodies to HSV, respectively, according to the manufacturer's instructions [Kawana et al, 1995;Hashido et al, 1997;Kumaki et al, 2001]. Antibody index values were calculated by dividing the optical density values for test specimens by the average of the optical density values for the standard pooled human serum containing low-titer IgG and IgM-type antibody to HSV, respectively.…”
Section: Serologic Studiesmentioning
confidence: 99%